1998
DOI: 10.1103/physrevd.58.105009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of glueball masses from supergravity

Abstract: In the framework of the conjectured duality relation between large N gauge theory and supergravity the spectra of masses in large N gauge theory can be determined by solving certain eigenvalue problems in supergravity. In this paper we study the eigenmass problem given by Witten as a possible approximation for masses in QCD without supersymmetry. We place a particular emphasis on the treatment of the horizon and related boundary conditions. We construct exact expressions for the analytic expansions of the wave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
115
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 22 publications
14
115
0
Order By: Relevance
“…(3.5) 14 In order to keep equations uncluttered, we adopt simple overall normalizations in Eqs. (3.1), (3.6), but keep all later equations normalized with respect to these.…”
Section: Example: Bosonic String Tachyonsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3.5) 14 In order to keep equations uncluttered, we adopt simple overall normalizations in Eqs. (3.1), (3.6), but keep all later equations normalized with respect to these.…”
Section: Example: Bosonic String Tachyonsmentioning
confidence: 99%
“…A better model would have a smooth minimum. For example, consider the variant 14) combined with an orbifolding u → −u. The potential has been designed to have the same large-u behavior and the same minimum as before.…”
Section: Regge Trajectories At T >mentioning
confidence: 99%
See 1 more Smart Citation
“…This study was pioneered by [9] and afterwards the spectrum was completed in [10]- [13]. As mentioned in the previous section, the computation of correlation functions amounts -using the gauge/gravity duality-to solving field equations for the corresponding fluctuation in the AdS background.…”
Section: Black-hole Backgroundsmentioning
confidence: 99%
“…The spectrum is found to be discrete and exhibits a mass gap. In [9], [10] the authors found that the mass of the 0 ++ and its excited states is given by, …”
Section: Black-hole Backgroundsmentioning
confidence: 99%